RELATIONSHIP BETWEEN SEDIMENT ORGANIC MATERIAL CONTENT WITH THE ABUNDANCE OF Cerithidea obtuse IN THE INTERTIDAL ZONE, BUKIT BATU DISTRICT, BENGKALIS REGENCY, RIAU - Parapat, Monica Esra; Nasution, Syafruddin; Zulkifli, Zulkifli (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
This study was carried out in March-April 2024 in the intertidal zone of Bukit Batu District, Bengkalis Regency, Riau Province, to know the size distribution and the relationship between sediment organic matter content and the abundance of Cerithidea obtuse. This research uses a survey method by determining sampling stations using purposive sampling of three stations. Each station has three transects consisting of plots measuring 3 m2. The Kruskal-Wallis test was carried out to determine differences in abundance and the relationship between sediment organic matter content and the abundance of C. obtuse. Statistical correlation and linear regression tests were carried out. The results showed that the organic matter content of the sediment is included in the medium-high category, ranging from 15.01%-20.77%. The abundance of C. obtuse ranged between 5.12−6.96 ind/m2. There were differences in the abundance of C. obtuse among stations, with details between stations 3 and 1 and stations 3 and 2 being significant, while between stations 1 and 2 it was not significant. There were no differences in the abundance of C. obtusa among intertidal subzones. The distribution of C. obtuse is clustered with a dominant size of 20.7−34.5 mm. There is a moderate relationship between sediment organic matter content and the abundance of C. obtusa with a correlation coefficient (r) of 0.573, which is interpreted in the equation Y = 0.353X + 12.146.